Chitosan Membrane Modified With a New Zinc(II)-Vanillin Complex Improves Skin Wound Healing in Diabetic Rats - de Aragão Tavares, Emanuella; de Medeiros, Wendy Marina Toscano Queiroz; de Assis Pontes, Talita Pereira; Barbosa, Maisie Mitchele; de Araújo, Aurigena Antunes; de Araújo, Raimundo Fernandes; Figueiredo, Jozi Godoy; Leitão, Renata Carvalho; da Silva Martins, Conceição; da Silva, Francisco Ordelei Nascimento; de Brito Pontes, Ana Cristina Facundo; de Lima Pontes, Daniel; et al. (Frontiers in Pharmacology, 2019)
The treatment of chronic wounds is considered a public health problem. When the condition affects at-risk groups such as those with diabetics, it becomes a great clinical challenge. In this work, we evaluated the healing effects of a new zinc complex, [Zn(phen)(van)2], identified as ZPV, which was synthesized, characterized and associated with chitosan (CS) membranes and tested on cutaneous wounds of diabetic rats. Chitosan membranes were modified by Schiff base reaction with the complex under two experimental conditions (14 and 21 days), resulting in membranes with concentrations of complex equal to 7.36 x 10-7 mol cm-2 (CS-ZPV1) and 1.22 x 10-6 mol cm-2 (CS-ZPV2). Release assays in aqueous medium indicated that the membranes release the complex gradually when exposed to an aqueous medium. Diabetes was inducted in Wistar rats using 40 mg/kg (i.v.) streptozotocin. On the seventh day after diabetic induction, a circular excision on the skin (1.0 cm) was performed with a punch. The lesions were treated with the pure chitosan membrane and the membrane associated with the zinc-vanillin complex in two different doses. Skin samples were subjected to macroscopic and histopathological analyses, cytokine (TNF-α, IL-1β and IL-10) quantification and reverse transcriptase polymerase chain reaction (TGF-β and VEGF) assays. The analyses showed a decrease in wound size, reepithelialization, angiogenic stimulus, collagen deposition, and reduced levels of TNF-α and IL-1β as well as increased IL-10 and gene expression of TGF-β and VEGF. The evaluated parameters suggest that CS-ZPV in the two concentrations tested may be effective in the treatment of chronic wounds.